Herniated Nucleus Pulposus in Dr. Hasan Sadikin General Hospital Bandung Indonesia - Ikhsanawati, Annisa; Tiksnadi, Bambang; Soenggono, Arifin; Hidajat, Nucki Nursjamsi (Althea Medical Journal, 2015)
Background: Herniated nucleus pulposus (HNP) is one of the most common diseases of the spine. For anÂ optimal management and prevention, thereâs a need for data on factors related to the onset of complaintsÂ because this disease lowers the quality of life and increases morbidity. This study is aimed to see the scaleÂ and pattern of the HNP in Dr. Hasan Sadikin General Hospital, Bandung.Methods: This is a descriptive study with the design of case series, data was obtained from medical recordsÂ of patients with the diagnosis of HNP in the inpatient care of Dr. Hasan Sadikin General Hospital in theÂ period of 2007â2011.Results: According to the study on 79 patients, with 43 men and 36 women, the highest incidence was atÂ the age group of 51â60 years old (31.6%) and most common occupation was civil servant (11.4%). TheÂ most common clinical symptoms were sciatica (51.9%) and low back pain (51.9%). Most frequent locationÂ was in the lumbar vertebrae at the level of L5âS1 (58.2%). Trauma was found to be the highest relatableÂ history in the patients (39.2%). Therapy of choice was primarily conservative (58.2%) and most patientsÂ went home after the progression (84.8%). The year 2007 showed the highest prevalence of HNP at 25.3%.Â The most common clinical symptoms were sciatica (51.9%) and low back pain (51.9%)Conclusions: The most common clinical symptoms were sciatica and low back pain. Most frequent locationÂ was in the lumbar vertebrae at the level L5âS1. [AMJ.2015;2(1):179â85]